Relasi Mitos terhadap Pelestarian Lingkungan Hidup dalam Dua Novel Anak Okky Madasari: Tinjauan Antropologi Sastra - Burhanuddin, Ahmad (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
The environment is important for human life. Most environmental damage is caused by humans because humans play an important role in determining the future of the environment. Local communities have ways of utilizing natural rights to protect the environment, one of which is through environmental myths. Through myths, society builds a culture that is useful for environmental sustainability. Okky Madasari's novel highlights myths that play an important role in environmental sustainability. These myths function to dispel crimes against the environment from irresponsible human behavior. This research aims to look for the relationship between myth and environmental sustainability contained in two novels by Okky Madasari, namely Mata di Tanah Melus and Mata and Laut Man. This type of research is qualitative. This research was carried out using a literary anthropology approach by studying the myths in Okky Madasari's two novels and then describing the positive relationship of these myths to environmental sustainability. Data collection techniques use library techniques. The data analysis technique uses content analysis techniques. The results of this research explain that myths have a role in environmental conservation efforts. The relationship between myth and environmental sustainability is a consideration for humans to always maintain a good relationship with nature because in essence humans are only a small part of the ecosystem. In the novel Mata di Tanah Melus, the myth about Bei Nai, or the Crocodile God is found. Fear of Bei nai figures can limit the level of crocodile hunting. In the novel Mata and the Sea Man, a myth is also found about the prohibition of fishing on full moon nights, because on that night many fish breed. With this myth, the fish breeding cycle is maintained.